(untitled) (Global Journal of Management and Business Research, 2017)
Entrepreneurship has been recognize as an instrument for Nigerian youth to acquire basic managerial skills and to use that skilled acquired to be sustainable self-employment and to the Nation Development This paper examines the challenges of entrepreneurship to vocational and technical Education However its vision the need to emphasize entrepreneurship at the phases of education as this will go extra miles in improving the socio-economic as well as socio-political problems such as unemployment poverty among others that are threat to the nation security Entrepreneurship is introduce to less socio-economic problems and will aid to job creation poverty alleviation reduction in unemployment developing youth enterprise and technological development to Nigerian education Those who have less education but have more practical experience and training enter into the industry early leaving the educated once with little or no experience patterning skill acquisition behind However in such cases less education restricts the growth and development of the enterprise It is however recommended that entrepreneurship should be taught well in all phases of education especially vocational and technical education as a tool to transformation agenda to the nation and the world at large